Advances in management accounting. Vol. 29 - Malina, Mary A. (Emerald Publishing Limited, 2017)
Advances in Management Accounting (AIMA) is a publication of quality applied research in management accounting. The journal's purpose is to publish thought-provoking articles that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. The journal seeks thoughtful, well-developed articles on a variety of current topics in management accounting, broadly defined. All research methods including survey research, field tests, corporate case studies, experiments, meta-analyses, and modeling are welcome. Some speculative articles, research notes, critiques, and survey pieces will be included where appropriate. Articles may range from purely empirical to purely theoretical, from practice-based applications to speculation on the development of new techniques and frameworks. Empirical articles must present sound research designs and well-explained execution. Theoretical arguments must present reasonable assumptions and logical development of ideas. All articles should include well-defined problems, concise presentations, and succinct conclusions that follow logically from the data.
Prelims -- Changes in cost system design and intensity of use in times of crisis: evidence from Dutch local government -- Beyond budgeting: distinguishing modes of adaptive performance management -- Assessing the main and interaction effects of activity-based costing and internal and external information systems integration on manufacturing plant operational performance -- An exploratory investigation of management accounting service quality dimensions using Servqual and Servperf -- Learning from the experience of others: lessons on the research - practice gap in management accounting - A nursing perspective -- Performance changes over difficult times for the banking sector: a branch level study -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Managerial accounting; Business & Economics -- Accounting -- Managerial; Management accounting & bookkeeping